Colon capsule endoscopy versus CT colonography in FIT-positive colorectal cancer screening subjects: a prospective randomised trial—the VICOCA study - González-Suárez, Begoña; Pagés, Mario; Araujo, Isis Karina; Romero, Cristina; Rodríguez de Miguel, Cristina; Ayuso, Juan Ramón; Pozo, Àngels; Vila-Casadesús, Maria; Serradesanferm, Anna; Ginès, Àngels; Fernández-Esparrach, Glòria; Pellisé, Maria; et al. (BMC medicine, 2020)
Background Colon capsule endoscopy (CCE) and CT colonography (CTC) are minimally invasive techniques for colorectal cancer (CRC) screening. Our objective is to compare CCE and CTC for the identification of patients with colorectal neoplasia among participants in a CRC screening programme with positive faecal immunochemical test (FIT). Primary outcome was to compare the performance of CCE and CTC in detecting patients with neoplastic lesions. Methods The VICOCA study is a prospective, single-centre, randomised trial conducted from March 2014 to May 2016; 662 individuals were invited and 349 were randomised to CCE or CTC before colonoscopy. Endoscopists were blinded to the results of CCE and CTC. Results Three hundred forty-nine individuals were included: 173 in the CCE group and 176 in the CTC group. Two hundred ninety individuals agreed to participate: 147 in the CCE group and 143 in the CTC group. In the intention-to-screen analysis, sensitivity, specificity and positive and negative predictive values for the identification of individuals with colorectal neoplasia were 98.1%, 76.6%, 93.7% and 92.0% in the CCE group and 64.9%, 95.7%, 96.8% and 57.7% in the CTC group. In terms of detecting significant neoplastic lesions, the sensitivity of CCE and CTC was 96.1% and 79.3%, respectively. Detection rate for advanced colorectal neoplasm was higher in the CCE group than in the CTC group (100% and 93.1%, respectively; RR = 1.07; p = 0.08). Both CCE and CTC identified all patients with cancer. CCE detected more patients with any lesion than CTC (98.6% and 81.0%, respectively; RR = 1.22; p = 0.002). Conclusion Although both techniques seem to be similar in detecting patients with advanced colorectal neoplasms, CCE is more sensitive for the detection of any neoplastic lesion. Trial registration ClinicalTrials.gov Identifier: NCT02081742 . Registered: September 16, 2013.